Stress Analysis on Hemispherical Head of Internal Pressure Vessel - Mengzhao Long; Zhanhui Wang; Zhifang Zhang; Xiaojun Li (Journal of Engineering)
Since there is no unified equation of calculated stress near the marginal zone of cylindrical shell and its connected hemispherical head, this article first deduces calculated stress calculation equation near the marginal zone of hemispherical head according to the continuity equation, marginal load, marginal moment, flexural force, and internal pressure. Moreover, tested stress is tested by the pressure vessel stress testing device, by comparing and analyzing calculated stress and tested stress to check the exactitude and serviceability of torque calculated stress equation near the marginal zone of hemispherical head. The results show that away from the marginal zone, calculated stress and tested stress are basically unchanged, and the magnitude is basically the same, which is not affected by the marginal effect. Near marginal zone, calculated stress, and tested stress will suddenly change due to the marginal effect, but the error is within the allowable range. The variation trend of calculated stress is basically the same as that of tested stress; by contrasting and exploring calculated stress, tested stress, and FEM stress near the marginal zone of hemispherical head, exactitude and serviceability of torque calculated stress calculation equation near the marginal zone of hemispherical head are further verified.